A historical perspective of urban religion - Rodrigues Marques de Oliveira, Gabriela (Romanitas - Revista de Estudos Grecolatinos, 2023)
Urban Religion: A Historical Approach is a work that seeks to look at religions and the urban environment from new perspectives. Its availability in Portuguese thus offers a valuable opportunity for Brazilian and Lusophone researchers to reflect on religious and everyday aspects of ancient cities in the Mediterranean.
Keywords: Religion; Rome; Urbanism; Jörg Rüpke